Manufacture a Battery-like Supercapacitors with Electrodes of Graphene - Abdul-Rassol, Hend Kadhim; Abdul-Hussein, Adi Mahmoud (Iraqi Journal of Science, 2021)
A graphene-based battery-like supercapacitors (SC) were manufactured. The prime objective of this research was to use environmentally friendly and natural materials as possible for the SC electrodes, electrolytes and the separators. The SC were designed in cells like batteries, three types of plastic cases were used as SC cells; the electrode and electrolyte materials were mixed together and a solution formed and placed in the designed cell. The electrode material was graphene powder with different weights mixed with different volumes of electrolytes (which were: lemon juice, apple vinegar, H2SO4 and HNO3), and the separators used were Polytetrafluoroethylene polymer (PTFE) and cellulose based parchment paper (PP).Charging circuit was set, the cell SC charged with different charging rates and the voltage window was determined for each cell with different electrode/electrolyte/separator combination. Three of the fabricated cell SC were discharged through 0.5V LED light. The discharging rates were regular and the best was (1.22 volts discharged in 26 minutes). The capacitance of the discharged SC was calculated.Also the mixed solutions were tested by XRD analysis and the surface microscopy done by scanning electron microscope (SEM). The XRD spectra for the mixed solutions shows high crystallinity for the graphene with two distinct peaks at (002) and (004) direction.